2015
DOI: 10.1021/acs.orglett.5b00351
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Organocatalytic Aerobic C–H Oxidation of Amines with an ortho-Quinone Catalyst

Abstract: A simple bioinspired ortho-quinone catalyst for the aerobic oxidative dehydrogenation of amines to imines is reported. Without any metal cocatalysts, the identified optimal ortho-quinone catalyst enables the oxidations of α-branched primary amines and cyclic secondary amines. Mechanistic studies have disclosed the origins of different performances of ortho-quinone vs para-quinone in biomimetic amine oxidations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 57 publications
1
36
0
5
Order By: Relevance
“…123 Considering the critical roles of methoxyl, other alkoxy groups such as ethoxyl, iso-propoxyl and aryloxyl were investigated, but the obtained catalysts were less effective, and no activity was observed after removing the tert-butyl group of Q5. These results strongly revealed that the substituents played vital roles in tuning the activity of Q5 for amine oxidation and the regeneration of Q5 by molecular oxygen.…”
Section: Scheme 42 Scopes Of Q4 Red /Rhcnt-catalyzed Dehydrogenation mentioning
confidence: 99%
“…123 Considering the critical roles of methoxyl, other alkoxy groups such as ethoxyl, iso-propoxyl and aryloxyl were investigated, but the obtained catalysts were less effective, and no activity was observed after removing the tert-butyl group of Q5. These results strongly revealed that the substituents played vital roles in tuning the activity of Q5 for amine oxidation and the regeneration of Q5 by molecular oxygen.…”
Section: Scheme 42 Scopes Of Q4 Red /Rhcnt-catalyzed Dehydrogenation mentioning
confidence: 99%
“…7 Their reactivity can be finely tuned by substituents on the quinoidal ring, while their arrangement as either ortho-or para-isomer can have a dramatic impact on their overall physical properties. 8 An important sub-class of ortho-and para-quinones are those which bear oxygen substituents (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…[20] The potential synthetic utility of cofactor mimics of this type has recently been recognized and this has led to the development of new organocatalytic protocols for amine oxidation by Stahl (Scheme 2 b) [21] and others. [22][23][24]…”
Section: Introductionmentioning
confidence: 99%